Tingkat Kesejahteraan Keluarga Nelayan pada Masa Pandemi Covid-19 di Kelompok Nelayan “Astitining Segara” Kelurahan Sanur, Kecamatan Denpasar Selatan - MBARAANTI, ANGGRANI MARTAN; DEWI, RATNA KOMALA; DARMAWAN, DWI PUTRA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
The Level of Welfare of Fishermen's Families during the covid-19 pandemic in the Fishermen's Group